PENERAPAN TECHNOBREEDING TERNAK KAMBING BAGI MASYARAKAT DESA TEMPAK, CANDIMULYO, MAGELANG - Setyo Utomo; Nur Rasminati (LPPM IST AKPRIND Yogyakarta, 2020)
In general, the poor try to increase their income by raising livestock especially goat from “gaduhan”. This community service activity aims to increase income through raising goat by applying technobreeding to obtain optimal production. The activity was held for one year, namely 2019 in Tempak village, Candimulyo sub-district, Magelang regency. Tempak Village is a priority for overcoming poor villages in Magelang district. Through the application of these two technologies, it was hoped that more healthy breeders and productive breeders would be produced. There were 30 poor farmers with an average of one goat. Methods of applying technology through awareness, training and mentoring. In general theywere very enthusiastic about this technologies, because they were very aware of the results in order to obtain profitable production. It was concluded that the community has the awareness and ability to implement technobreeding to increase the productivity of goat.